Analisis Dampak Ekstrakurikuler Drumband terhadap Pengembangan Kreativitas dan Kecerdasan Emosional Siswa Sekolah Dasar - Titin Nurrohmat; Nisha Fitria; Tiara Dwi Putri; Desi Karunia Cibro; Adriana Meidy Taura Batubara; Afridha Laily Alindra; Elsa Mutmainah (Jurnal Lensa Pendas, 2025)
This study examines the role of drumband extracurricular activities in developing creativity and emotional intelligence of elementary school students at UPTD SDN Purwamekar, Purwakarta, which contributes to the improvement and creativity of students' emotional intelligence at the elementary school level. Extracurricular activities such as drumband are not only a means of developing talent, but also act as a medium for forming students' character and social skills from an early age. Data collection was conducted through interviews with supervising teachers and questionnaires filled out by 15 students in grades IV and V who actively participated in drumband activities for one semester. The data analysis technique was carried out descriptively qualitatively by grouping findings based on indicators of students' creativity and emotional intelligence. The results of the study showed that drumband activities had a significant positive influence on the development of students' creativity; as many as 86.6% of respondents stated that they were able to channel creative ideas and dare to express themselves through music. In addition, all respondents (100%) stated that they experienced improvements in terms of emotional management and teamwork, which are very important in the learning process in elementary schools. The results of this study were also supported by teachers who saw an increase in students' self-confidence, discipline, and social skills during the activities. Based on the research results, drumband extracurricular activities are a useful means to develop 21st century skills, such as critical and collaborative thinking, in addition to honing musical talents. The recommendations of this study include the need for further research to examine the elements that contribute to the success of drumband extracurricular activities and the implementation of other art extracurricular programs at the elementary school level